Microscopically characterizing cells - Morrey, John D; Lowry, William (Utah : Taped Technologies, 1992)
Showing the characteristics of cells. Aspects of the culture cells that have been explain are, artifacts, morpholoy, size, growth patterns, cellular definition and confluency (growth rate)
Keywords: Cell culture; Cells -- Growth; Cells -- Morphology